Low-temperature fabrication of crystalline MnCoO spinel film on porous carbon paper for efficient oxygen evolution reaction. Issue 29 (12th March 2021) - Kwon, Sunglun; Lee, Ha Eun; Han, Donghoon; Lee, Jong Hyeon
Abstract : A thin film of MnxCo3− x O4 (MnCoO) nanocatalyst on a porous carbon fiber paper (CFP) electrode for efficient oxygen evolution reaction (OER). Abstract : Cubic Mn x Co3− x O4 ( x = 0–0.5) spinel nanocrystal thin films were fabricated on carbon fibre electrodes via one-step topotactic catalysis using Co(OH)2 nanosheets under aqueous and mild reaction conditions (<120 °C). The MnCo3 O4 ( M n = 0.01)/CFP catalyst showed the best charge transport efficiency, exhibiting excellent OER activity and stability.